2015
DOI: 10.1021/acs.jpcc.5b06313
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Exchange in MnII[TCNE] (TCNE = Tetracyanoethylene) Molecule-Based Magnets with Two- and Three-Dimensional Magnetic Networks

Abstract: The chemical bond and its role as a mediator of magnetic exchange interaction remains a crucial aspect in the study of molecular magnetism. Within the M[TCNE] (M = 3d metal; TCNE = tetracyanoethylene) class of organic-based magnets, only V [TCNE] x (x ∼ 2) orders magnetically above room temperature (T c ∼ 400 K), while structural factors underlying this exceptional behavior remain elusive. Conversely, Mn-[TCNE] complexes of diverse crystal structure have recently become available, e.g., 2D-layer [Mn(TCNE)(NCM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 63 publications
0
6
0
Order By: Relevance
“…In section , we focus on surveying current examples of framework magnets based on organic radical linkers, including nitroxides, organonitriles, and semiquinoid derivatives. Note that this last class of compounds has provided the MOF magnets with the highest reported ordering temperature of 171 K. Within all sections, we adopt the notation of the form I m O n to describe the inorganic and organic dimensionality of the structures, where m and n represent the dimensionality of the inorganic and organic connectivity, respectively, as introduced by Cheetham, Rao, and co-workers. , Finally, section provides an outlook for the field and discusses some potential strategies for increasing the ordering temperatures of MOF magnets above room temperature while retaining structural integrity and other functionality.…”
Section: Introductionmentioning
confidence: 99%
“…In section , we focus on surveying current examples of framework magnets based on organic radical linkers, including nitroxides, organonitriles, and semiquinoid derivatives. Note that this last class of compounds has provided the MOF magnets with the highest reported ordering temperature of 171 K. Within all sections, we adopt the notation of the form I m O n to describe the inorganic and organic dimensionality of the structures, where m and n represent the dimensionality of the inorganic and organic connectivity, respectively, as introduced by Cheetham, Rao, and co-workers. , Finally, section provides an outlook for the field and discusses some potential strategies for increasing the ordering temperatures of MOF magnets above room temperature while retaining structural integrity and other functionality.…”
Section: Introductionmentioning
confidence: 99%
“…Diluted magnetic oxides and semiconductors, such as cobalt-doped titania and manganese-doped zinc oxide or cadmium selenide, in the form of nanocrystals and quantum dots, represent different patterns of ligand arrangement and crystal-field splitting and exhibit new spectral features contributed by the dopant TM ions . Approaches and results of this work have potential for further application in identification of mechanisms for basic photoinduced processes in magnetically doped quantum dots or molecular magnets for information storage applications. ,, Magnetic molecular crystals and magnetic metalorganic frameworks , also exhibit variable coordination patterns of TM ions to neighboring ligands that may allow the design of new spin-crossover materials.…”
Section: Discussionmentioning
confidence: 89%
“…52 Approaches and results of this work have potential for further application in identification of mechanisms for basic photoinduced processes in magnetically doped quantum dots or molecular magnets 53 for information storage applications. 54,55,56 Magnetic molecular crystals 57 and magnetic metalorganic frameworks 58,59 also exhibit variable coordination patterns of TM ions to neighboring ligands that may allow the design of new spincrossover materials. a G: Grubbs' value was calculated on a sample including the bold items plus one.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the high electron affinity (2.77 ± 0.09 eV) and strong bonding capacity of TCNE make it particularly amenable to receive electrons. TCNE-based nanostructures have demonstrated interesting motifs, exotic properties, and promising applications. Lots of articles have reported that TCNE-based materials can be used as molecular magnets for spintronic applications , and as doping molecules to modify the electronic properties for semiconductor applications . Additionally, the TM-tetracyanoquinodimethane (TM-TCNQ), similar to the TM-TCNE system, has been used as an efficient electrocatalyst. , Thus, 2D TCNE-based nanosheets might be good candidates for eNRR.…”
Section: Introductionmentioning
confidence: 99%